Konstruksi Sosial Keberadaan Jemaat Ahmadiyah di Kota Medan - Indriani, Eva; Irwansyah, Irwansyah; Ismail, Ismail (Islam & Contemporary Issues, 2022)
This research aims to examine the social construction of the community regarding the presence of the Ahmadiyya Community in the city of Medan. The presence of the Ahmadiyya Community in Medan is unlike in other areas outside the North Sumatra province. They face intolerance, leading to persecution and even loss of lives. This research employs a qualitative research method, where the researcher directly observes the community and seeks to understand the social construction of the presence of the Ahmadiyya Community in Medan. Informants in this study include the Ahmadiyya Community preachers in Medan, the Chairman of the Interfaith Harmony Forum (FKUB) in Medan, the Indonesian Ulema Council (MUI) in Medan, the head of the neighborhood where the Ahmadiyya Community resides, the head of the neighborhood near the Mubarak Mosque, and the people around the residence of the Ahmadiyya Community and the Mubarak Mosque.